Utilization of stagnant non-potable pond water for cultivating oleaginous microalga Chlorella minutissima for biodiesel production. (October 2018) - Arora, Neha; Patel, Alok; Pruthi, Parul A.; Poluri, Krishna Mohan; Pruthi, Vikas
Abstract: Utilization of waste resources to cultivate microalgae for biofuel production has the potential to improve the economics along with sustainable reuse of discarded nitrogen and phosphorous sources. The present investigation aims to cultivate an oleaginous microalga ( Chlorella minutissima) in stagnant non-potable pond (SNP) water collected from different seasons (summer, winter and rainy) for biomass and lipid synthesis. The C. minutissima showed enhanced biomass productivity (245 mg/L/d) and lipid content (47 %) when grown in SNP water as compared to basal media, synthetic wastewater and recycled media respectively. The adaption in the SNP media by C. minutissima was attributed to an increase in cell size (∼2 folds) with decrease in total protein content (∼2 folds) and total carbohydrate content (∼1 fold) respectively. The fatty acid profile indicated the presence of C16:0, C16:2, C18:0, C18:1 and C18:2 as major methyl esters in the derived biodiesel. Further, the measured biodiesel properties such as specific density (0.90 g/cm 3 ), kinematic viscosity (3.24 mm 2 /s), flash point (143 °C), iodine value (40.14 g I2 /100 g) and acid value (3.24 mgKOH/g) abided by the ASTMD6751-02 andEN14214 standards. Therefore, such kind of SNP's have dual advantage; microalgal cultivation for biodiesel production and providing economical solution for bioremediation. Highlights: Enhanced lipid productivity in C. minutissima grown in stagnant non-potable pond (SNP) water. Alterations in protein and carbohydrate revealed adaption of microalga in SNP water. FAME analysis revealed predominance of C16:0, C18:1 and C18:2 . Biodiesel properties abided with ASTMD6751-02 andEN14214 standards. Stagnant non-potable pond water as a sustainable and cost effective cultivation media.